Nilai Perusahaan Dilihat dari Aspek Kebijakan Deviden, Ukuran Perusahaan, Profitabilitas dan Struktur Modal pada Sub Sektor Pertambangan Batu Bara yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Suci Budining Kisprasetiyani; Amalia (Economic Reviews Journal, 2025)
This study is aimed at analyzing the influence of dividend policies, company size, profitability and capital structure on the value of companies in the coal mining subsector list IDX for the period 2019-2023. The method for taking samples is in the form of purposive sampling. The total sample observed amounted to 75 data. As for the use data, the researcher uses secondary data, namely dividen policy data (DPR), company size (SIZE), profitability (ROA), capital structure (DER) and company value (PBV). In analyzing the data, Panel data regresion analysis is used. The data procesing is seconded through Eviews 12. The findings of the study indicate that dividend policy affects negatively and insignificantly, company size affects negatively, profitability affects positively and significantly, and capital structur affects positively. For the overall outcome of the variables (DPR, SIZE, ROA, DER, and PBV), it affects simultaneously the company's value. This study is aimed at analyzing the influence of dividend policies, company size, profitability and capital structure on the value of companies in the coal mining subsector list IDX for the period 2019-2023. The method for taking samples is in the form of purposive sampling. The total sample observed amounted to 75 data. As for the use data, the researcher uses secondary data, namely dividen policy data (DPR), company size (SIZE), profitability (ROA), capital structure (DER) and company value (PBV). In analyzing the data, Panel data regresion analysis is used. The data procesing is seconded through Eviews 12. The findings of the study indicate that dividend policy affects negatively and insignificantly, company size affects negatively, profitability affects positively and significantly, and capital structur affects positively. For the overall outcome of the variables (DPR, SIZE, ROA, DER, and PBV), it affects simultaneously the company's value.